Harmony Search and Nature Inspired Optimization Algorithms Theory and Applications, ICHSA 2018 - Yadav, Neha.; Yadav, Anupam; Bansal, Jagdish Chand; Deep, Kusum; Kim, Joong Hoon.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book covers different aspects of real-world applications of optimization algorithms. It provides insights from the Fourth International Conference on Harmony Search, Soft Computing and Applications held at BML Munjal University, Gurgaon, India on February 7-9, 2018. It consists of research articles on novel and newly proposed optimization algorithms; the theoretical study of nature-inspired optimization algorithms; numerically established results of nature-inspired optimization algorithms; and real-world applications of optimization algorithms and synthetic benchmarking of optimization algorithms.
Keywords: Computational intelligence; Computer vision; Data mining; Computational Intelligence; Computer Vision; Data Mining and Knowledge Discovery